Therapeutic potential of indoor climbing: from physical fitness to neurorehabilitation and mental health - Pluszyński, Tomasz; Padula, Natalia; Piotrowski, Karol; Jerczak, Małgorzata; Piórkowska, Iga; Przybył, Filip; Polewka, Mikołaj; Polańska , Aleksandra; Paczosa , Kacper (Quality in Sport, 2026)
Background Rock climbing is experiencing a global surge in popularity, integrating resistance and isometric training with high neurological stimulation. It challenges the traditional dichotomy between cardiovascular and strength sports by offering a complex, interval-based exertion where movement precision is as vital as power. Aim This review explores rock climbing as a health intervention, focusing on physiological adaptations, musculoskeletal health, and therapeutic efficacy in psychiatry and neurorehabilitation. Material and Methods This paper reviews recent literature, including meta-analyses and randomized controlled trials. The analysis covers physiological parameters (VO2 max, bone density, core strength), Bouldering Psychotherapy (BPT) for depression, neurorehabilitative protocols for Parkinson’s disease, Multiple Sclerosis, and Autism Spectrum Disorder (ASD), alongside an assessment of injury risks. Results Climbing significantly improves VO2 max, grip strength, and core stability, proving effective for chronic low back pain. In mental health, BPT reduces moderate depression symptoms (average 8.3-point decrease on the MADRS), achieving outcomes comparable to Cognitive Behavioral Therapy with long-term sustainability. In neurorehabilitation, climbing reduces Parkinson’s motor symptoms (tremor by 51%, rigidity by 30%), aids fatigue management in Multiple Sclerosis, and enhances selective attention in children with ASD. Overuse injuries, particularly to the finger pulley system, remain the primary risk factor (up to 68% of adult injuries). Conclusions Rock climbing is a safe, multi-modal intervention offering significant physiological, psychological, and neurological clinical benefits. It shifts patient identity from limitations to capabilities, warranting integration into standard healthcare. However, clinicians must remain vigilant regarding overuse injuries and skeletal maturity in adolescents.